SARS-CoV-2 Initiates Programmed Cell Death in Platelets. Issue 6 (3rd September 2021) - Koupenova, Milka; Corkrey, Heather A.; Vitseva, Olga; Tanriverdi, Kahraman; Somasundaran, Mohan; Liu, Ping; Soofi, Shaukat; Bhandari, Rohan; Godwin, Matthew; Parsi, Krishna Mohan; Cousineau, Alyssa; Maehr, René; et al.
Abstract : Rationale: Coronavirus disease 2019 (COVID-19) is characterized by increased incidence of microthrombosis with hyperactive platelets sporadically containing viral RNA. It is unclear if SARS-CoV-2 (severe acute respiratory syndrome, corona virus-2) directly alters platelet activation or if these changes are a reaction to infection-mediated global inflammatory alterations. Importantly, the direct effect of SARS-CoV-2 on platelets has yet to be studied. Objective: To characterize the direct SARS-CoV-2–platelet interactions using in vitro studies with purified infectious virions and samples from infected patients. Methods and Results: Platelet RNA analyzed by ARTIC v3 sequencing for SARS-CoV-2 showed presence of fragmented viral genome in all patients with COVID-19. Immunofluorescent imaging of platelets from patients with COVID-19 confirmed presence of SARS-CoV-2 proteins, whereas there was no detection of viral RNA by real-time quantitative polymerase chain reaction. Transmission electron microscopy of platelets incubated with purified SARS-CoV-2 virions demonstrated rapid internalization and digestion leading to distinct morphological changes and resulted in a release of extracellular vesicles. Interactions between SARS-CoV-2 and platelets occurred with or without ACE (angiotensin-converting enzyme) 2 presence as measured by immunofluorescence. Transmission electron microscopy showed that SARS-CoV-2 virions became internalized when they were attached to microparticles, bypassing the need for ACE2. Enrichment analysis of platelet transcriptome from patients with acute COVID-19, compared with those with clinical thrombosis, suggested upregulation of pathways related to virally mediated cell death, specifically necroptosis and apoptosis. Platelets incubated with infectious virus appeared to undergo cell death in 30 minutes postincubation as assessed by transmission electron microscopy and platelets from patients with COVID-19 showed evidence of increased markers of apoptosis and necroptosis by Western blot. Immunofluorescence confirmed colocalization of SARS-CoV-2 with phospho-MLKL (mixed lineage kinase domain-like pseudokinase) and caspase 3 on nonpermeabilized platelets in vitro and in COVID-19 platelets. Conclusions: Platelets internalize SARS-CoV-2 virions, directly or attached to microparticles, and viral internalization leads to rapid digestion, programmed cell death, and extracellular vesicle release. During COVID-19, platelets mediate a rapid response to SARS-CoV-2 and this response can contribute to dysregulated immunity and thrombosis. Abstract : Supplemental Digital Content is available in the text.